The relationship between phonological awareness and reading errors of the second-graders - Stelkic, Milica (Norma, 2022)
Reading consists of processing written data which are transmitted by text and thus reading is seen as a complex language skill. A prerequisite for the development of reading skills is developing phonological awareness and forming verbal representations. Success in solving tasks of phonological awareness is a predictor of reading abilities. For those reasons, this research attempts to determine the connection and mutual influence between these abilities. The research is designed as a cross-sectional study and it was conducted at Primary School «Dušan Radović» in Novi Sad from February to March 2020. The research sample consisted of 31 students (19 boys and 12 girls) whose average age was 8 years and 8 month. The included assessment instruments were the Three-dimensional Reading Test - «Samo jedan snežni dan» and the «FONT» test used for assessing phonological awareness. The findings of this research confirm the correlation between phonological awareness and reading errors in second-grade students. On the basis of this research, it can be concluded that there is a significant correlation between phonological awareness and reading ability and that their mutual influence is reciprocal, i.e. the development of one ability is a prerequisite for the development of the second one.